Interaction between secondary mitral regurgitation and left atrial function and their prognostic implications after cardiac resynchronization therapy. (28th July 2022) - Stassen, Jan; Galloo, Xavier; Hirasawa, Kensuke; van der Bijl, Pieter; Leon, Martin B; Marsan, Nina Ajmone; Bax, Jeroen J
Abstract: Aims: Left atrial (LA) function is a strong prognostic marker in patients with heart failure and functional mitral regurgitation (MR). Although cardiac resynchronization therapy (CRT) has shown to improve MR severity, the interaction between a reduction in MR severity and an increase in LA function, as well as its association with outcomes, has not been investigated. Methods and results: LA reservoir strain (RS) was evaluated with speckle tracking echocardiography in patients with at least moderate functional MR undergoing CRT implantation. MR improvement was defined as at least 1 grade improvement in MR severity at 6 months after CRT implantation. The primary endpoint was all-cause mortality. A total of 340 patients (mean age 66 ± 10 years, 73% male) were included, of whom 200 (59%) showed MR improvement at 6 months follow-up. On multivariable analysis, an improvement in MR severity was independently associated with an increase in LARS (odds ratio 1.008; 95% confidence interval 1.003–1.013; P = 0.002). After multivariable adjustment, including baseline and follow-up variables, an increase in LARS was significantly associated with lower mortality. MR improvers showing LARS increasement had the lowest mortality rate, whereas outcomes were not significantly different between MR non-improvers and MR improvers showing no LARS increasement ( P = 0.236). Conclusion: A significant reduction in MR severity at 6 months after CRT implantation is independently associated with an increase in LARS. In addition, an increase in LARS is independently associated with lower all-cause mortality in patients with heart failure and significant functional MR. Graphical Abstract: Graphical Abstract